Evaluation of English Teaching Materials used at a Vocational High School Based on Cunningsworth’s Checklist - Yeli Nurhamsih; Syahrial Syahrial (Universitas Bengkulu, 2018)
English teaching material is really important, that is why a teacher should be able to select the right book to use on teaching and learning process. One of the ways is by evaluating the textbook. This study aims to evaluate the English teaching materials covering its language content, language skills, and topics, used at a Vocational High School based on Cunningsworth’s checklist. The data were taken by distributing checklist and conducting interview to one vice- principal who is also as a teacher of English and two English teachers at a Vocational High School. The data were analyzed by getting average and percentage. The methodology of the research is descriptive qualitative content analysis. Results showed that language content in the textbook viewed from criteria of good English teaching materials are poor. The textbook only covers little grammar and vocabulary. The language skills practiced in the textbook according to criteria of good English teaching materials are poor for they are in general content and limited activities. While, according to criteria of good English teaching materials, the topics introduced in the textbook are poor too. The topics covered in the textbook are general topics. It can be concluded that English teaching materials covering language content, language skills, and topics in the textbook are not appropriate for hotel accomodation students. As suggestion, the four skills should be integrated in the topics in order to give more importance to grammar and communication skills. The topics content that relate to hospitality and tourism department specially for hotel accomodation department should be provided and added so it will be meaningful for the learners espesially the learners of hotel accomodation.